Presentations plus : - Peoples, David A. (J. Wiley, 1992)
Includes updated material and new chapters on making group presentations as well as source materials (such as visual aids). Also adds up-to-date examples that will replace the outmoded ones in the current edition. Based on David Peoples' popular seminars on presentations and selling skills, it will show the reader the tricks and ordinary techniques that make up strong presentations. As with the first edition, this revision will cover areas of concern from preparing for a speech to keeping the audience interested and alert to reducing pre-presentation nervousness.